The Wondrous of Fungus World - Ishak, Wan Rosli Wan; Ng, Sze Han (Penerbit Universiti Putra Malaysia, 2017)
Mushrooms can be defined as “macrofungi” with distinctive fruiting bodies that could be hypogenous or epigeous, large enough to be seen by naked eyes and to be picked by hand (Chang & Miles, 1992). They contain no chlorophyll, therefore, do not have leaves, seeds or roots and in real do not need any light to grow. They are a group of fleshy macroscopic fungus which propagates by releasing spores in the dark and typically grew on its food source or on soil above ground. Through the process of fructification, the fruiting bodies are developed from spacious underground mycelia (hyphae). They require a substrate agricultural waste to absorb nutrition and produce enzymes which degrade complex organic matter (Walde et al., 2006). The estimated lifetime of fruiting bodies is only 10-14 days (Kalac, 2009).